PERANCANGAN BUSANA PRIA SIAP PAKAI DENGAN INSPIRASI RITUAL IOMANTE SUKU AINU - Maria Audrey Angkadiredja; Dewi Isma Aryani (Narada : Jurnal Desain dan Seni, 2022)
The Ainu are the indigenous people of the northern regions of the Japanese Archipelago, particularly Hokkaido, as well as Russia's Sakhalin Island and the Kuril Islands. Currently, the Ainu tribe in Hokkaido numbering about 20,000 people and adheres to the belief of spirits in every part of nature, inanimate objects, and so on. One of the Ainu cultures is the Iomante ritual, which is the ceremony of returning Kamui's spirit to the divine realm by sacrificing a bear which is considered the incarnation of Kamui himself. The uniqueness of the Iomante ritual of the Ainu Tribe inspired the design of a ready-to-wear clothing collection with manipulation details in the form of a blend of culture, typical Ainu motifs with the concept of modern men's clothing and suitable for urban communities. Typical Ainu motifs are applied to clothing using special Ainu embroidery techniques, namely Ainu running stitch and pleats. The method used is the PBL (Project Based Learning) method in the form of real project learning outcomes through information search and data synthesis, material exploration, feasibility assessment, and design interpretation into the product. The purpose of this design is to create a menswear collection inspired by the Ainu Iomante Ritual to produce a ready-to-wear menswear collection with strong, confident, and passionate characters. Thus, it is hoped that the results of designing the THE LOST TRIBE collection from the inspiration of the Iomante ritual can be a reference for modern men's clothing in Indonesia.